A STUDY ON THE CREATIVE SOCIAL EMOTIONAL LEARNING ENGLISH (CSELE) CLASSROOM MODEL IN INDONESIAN CONTEXT - Suganda, Lingga Agustina; Petrus, Ismail; Zuraida, Zuraida; Kurniawan, Dedi (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: This study aims to design the Creative Social Emotional Learning English (CSELE) classroom model in one of the district schools in South Sumatera, Indonesia. This model was proposed due to a growing awareness among educators and policymakers about the importance of social and emotional development for successful student. Based on the ADDIE model, the CSELE model is designed to include three steps: (1) the learning objective statement and need analysis, (2) the class strategy design, and (3) the class implementation and evaluation. The CSELE model focuses on integrating the efforts to support Social Emotional Learning (SEL) in the English as A Foreign Language (EFL) classroom context. This model involves the process of integrating the materials from the Indonesian 2013 national curriculum and creative teaching procedures for developing the students? social emotional competencies, which include self-awareness, self-management, social awareness, relationship skills, and responsible decision making. The findings showed that the CSELE model has demonstrated positive effects on the students? social emotional competence, academic motivation, and classroom climate. However, more qualitative and quantitative studies should be conducted for further implementation of this model. Keywords:  Social Emotional Learning (SEL), English as a Foreign Language (EFL), creative, teaching and learning